Isolation and identification of an isomeric sildenafil analogue as an adulterant in an instant coffee premix - Ahmad Yusri Mohd Yusop; Linda Xiao; Shanlin Fu (Oxford University Press, 2020)
The proliferation of adulterated health foods and beverages in the market demands a comprehensive analytical strategy to identify the adulterants, particularly those of isomeric phosphodiesterase 5 (PDE5) inhibitors. An instant coffee premix (ICP) purchased from an online retailer was flagged for suspected adulteration through PDE5 inhibition assay. The ICP was then analysed using suspected-target and non-targeted screenings of a liquid chromatography-quadrupole time-of-flight mass spectrometry. Based on these findings, a PDE5 inhibitor initially assigned as compound X was isolated from the ICP by employing a liquid chromatography-diode array detection before its structural elucidation with liquid chromatography-ultraviolet (LC-UV) spectroscopy and nuclear magnetic resonance (NMR) spectroscopy. The suspected-target screening matched the protonated molecule ([M + H]+) precursor ion of compound X at m/z 499.2310 with two suspected analytes that are structural isomers of one another. The fragmentation patterns of compound X were comparable to those analogues in the dithiocarbodenafil group through the non-targeted screening. These findings, complemented by the LC-UV and NMR spectroscopy data, together with the chromatographic separation of related structural isomers, conclude the identity of compound X. To our best knowledge, this is the first study to report the presence of 3,5-dimethylpiperazinyl-dithiodesmethylcarbodenafil in an ICP sample. Key points The herbal-based male sexual performance products' lucrative market has instigated their rampant adulteration, particularly with PDE5 inhibitors. The adulterated products may also contain analogues of the approved PDE5 inhibitors, which usually passed into the market undetected as they are not included in the routine targeted screening procedure. The present study detected, isolated, and identified an isomeric sildenafil analogue from an instant coffee premix sample using rapid qualitative assay and comprehensive analytical analysis. This paper highlighted the applicability of the established strategies for routine casework, particularly in a forensic drug testing laboratory.